The correct answer is it is a figure with at least 3 straight sides. When you think of a square or a triangle they both have at least 3 sides that are straight. A circle doesn't have any straight sides so it is not a polygon.
You can prove that the other answer is wrong because of two things:
The definition of a polygon is a plane figure with at least three straight sides.
Also, when you think of most shapes what do they all have in common? The have at least three straight sides
The solution is (3 , 4) ⇒ 2nd answer
Step-by-step explanation:
The system of equations can be solved by:
- Elimination method
- Substitution method
The system of equations is:
y = 3 x - 5 ⇒ (1)
y = x + 3 ⇒ (2)
By using the substitution method substitute y in equation (2) by equation (1)
3 x - 5 = x + 3
Subtract x from both sides
x = 8
Divide both sides by
x = 3
substitute x by 3 in equation (1)
y = 3(3) - 5
y = 9 - 5
y = 4
The solution is (3 , 4)
Learn more:
You can learn more about the system of equations in brainly.com/question/6075514
#LearnwithBrainly
The answer is d, just find the equation and then plug in the first few numbers of copies and you’ll find the correct answer
mark me brainliest if the answer is correct, thank you in advance :)
Answer: IX - 4I ≤ 4
Step-by-step explanation:
In the numer line we can see that our possible values of x are in the range:
0 ≤ x ≤ 8
And we want to find an absolute value equation such that this set is the set of possible solutions.
An example can be:
IX - 4I ≤ 4
To construct this, we first find the midpoint M of our set, in this case is 4.
Then we write:
Ix - MI ≤ IMI
Notice that i am using the minor and equal sign, this is because the black dots means that the values x = 0 and x = 8 are included, if the dots were empty dots, it would be an open set and we should use the < > signs.
Answer:
The equation for b would be y = 1/2x + 1
Step-by-step explanation:
In order to find this, start by finding two points on the line. We'll use (0,1) and (2, 2). From there we start by finding the slope.
m(slope) = (y2 - y1)/(x2 - x1)
m = (2 - 1)/(2 - 0)
m = 1/2
Now using that, we can plug it, along with a point into point-slope form to get the answer.
y - y1 = m(x - x1)
y - 1 = 1/2(x - 0)
y - 1 = 1/2x
y = 1/2x + 1